Gender difference in the authorship of top anesthesiology and pain journals: a protocol for retrospective bibliometric study - Bo Jiao; Liyun Deng; Mingyuan Chen (Frontiers in Medicine, 2026)
Introduction The number of women in medicine has increased, and female scientists play an important role in medical research. However, bias in research publication and funding persists, which may influence the representation of women in medical studies. This study aims to explore women's representation in the authorship of top-five high-impact anesthesiology and pain journals over the past ten years, particularly during the COVID-19 pandemic period. Methods This retrospective bibliometric study will be performed according to relevant reporting recommendations for observational studies. The five most influential anesthesia and pain management journals will be selected based on their impact factor and most recent H-index (2024 Journal Citation Reports). Two researchers will search the Web of Science (WOS) Core Collection database for publications in these journals between 1 January 2015 and 31 December 2024 based on the journal-title. Microsoft Excel 2016 and SPSS (version 26.0, IBM) will be used for data storage and analysis. Statistical analysis will be performed according to various purposes, and a regression model will be applied to investigate the correlation between different variables. Discussion The academic status of female authors in the fields of anesthesiology and pain medicine will be comprehensively summarized from multiple perspectives through this research. This study will identify the top-five anesthesiology and pain journals and analyze authorship gender disparities, providing key insights into women's contributions to the field and guiding future research.